Applications and impacts of nanotechnology in poultry nutrition - Babak Hosseintabar-Ghasemabad; Silvia Ondrašovičová; Olga Vilorievna Kvan; Elena Vladimirovna Sheida; Artem Vladimirovich Bykov; Alireza Seidavi; Desiderio Rodriguez Velazquez; Mona M. M. Y. Elghnadour; Deli Nazmín Tirado-González; Susanne Kreuzer-Redmer; Abdelfattah Z. M. Salem (Discover Applied Sciences)
Abstract The rapid expansion of the world population, intensifying environmental concerns and increasing demand for healthy food have created significant challenges for humanity that require multifaceted solutions in various areas. The poultry sector is one of the fastest-growing industries worldwide, playing an important role in ensuring food security and meeting nutritional and economic needs. Advances in poultry nutrition with the help of emerging nanotechnology can offer promising avenues to address the aforementioned challenges. This review report reviews nanotechnology and reports on strategies to optimize the use of nutrients, micronutrients, bioactive compounds, and minerals in poultry production with the help of this technology. Nanoscale material manipulation provides an opportunity for researchers to exploit the unique properties and functions of nanoscale materials to stimulate immunity, improve production efficiency, and promote overall flock health. Therefore, the increasing application of nanotechnology is considered a vital opportunity for sustainable growth in the poultry industry, food security, and environmental protection. If we recognize and are aware of the proper use of this technology and eliminate implementation barriers, risks, and potential concerns, we can make good use of it in the future successful vision of the poultry industry and achieve the ideal goals of the poultry industry.